2015
DOI: 10.1016/j.ajo.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Concentric Rings Method as a Topographic Measure of Retinal Nonperfusion in Ultra-Widefield Fluorescein Angiography

Abstract: 2 Structured Abstract Purpose:To validate the use of concentric rings as a method to measure topographical area of retinal non-perfusion in ultra wide-field angiography with the ischemic index method, which is the most frequently used method to measure non-perfusion in ultra widefield angiography. Design:Validation study and reliability analysis Methods:Setting: Single centre study performed at National Institute for Health Research Moorfields Biomedical Research Centre, London, United Kingdom.Study Population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…In order to assess spatial location and quantity of non-perfusion and area of new vessels, a concentric rings template was applied to each image in accordance with previously described methods. 80 In brief, this validated method incorporates a macular ring with a radius of 2.5 DDs and five additional concentric rings (rings 1-5), each with a 2.5-DD increment in radius. Each of the six rings (ring M and rings 1-5) was divided into 12 segments.…”
Section: Ultrawide Field Fundus Fluorescein Angiographymentioning
confidence: 99%
“…In order to assess spatial location and quantity of non-perfusion and area of new vessels, a concentric rings template was applied to each image in accordance with previously described methods. 80 In brief, this validated method incorporates a macular ring with a radius of 2.5 DDs and five additional concentric rings (rings 1-5), each with a 2.5-DD increment in radius. Each of the six rings (ring M and rings 1-5) was divided into 12 segments.…”
Section: Ultrawide Field Fundus Fluorescein Angiographymentioning
confidence: 99%
“…To determine whether the observed changes were due to the laser treatment or diabetes itself, the amount of ischemia was quantified using the mean perfused ratio. The mean perfused ratio was calculated by the concentric rings method utilized by Nicholson et al 19 Compared to the standard ischemic index method wherein the grader draws the ratio of area perfused to the total area graded, the concentric rings method utilizes a set template. It has a perfect agreement with the ischemic index method, a higher inter-grader agreement, and a short-grading time.…”
Section: Discussionmentioning
confidence: 99%
“…It has a perfect agreement with the ischemic index method, a higher inter-grader agreement, and a short-grading time. 19 Using the concentric rings method, it was observed that at 12 and 24 months post laser, PRP laser resulted in a significant increase in the perfusion of the eye, whereas the control eyes showed no change. The result suggests that although diabetes remains a contributing factor, the improvement and changes in ischemia are most likely the result of the laser treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentric rings template then was added to each image according to previously described methods. 26 This validated method incorporates a macular ring with a radius of 2.5 disc diameters (DD) and five additional concentric rings (rings 1-5), each with a 2.5 DD increment in radius. Each of the six rings (Rings M and 1-5) was divided into 12 segments.…”
Section: Image Processingmentioning
confidence: 99%